P05.89 Comparison of local control of brain metastases with stereotactic radiosurgery versus surgical resection: A secondary analysis of EORTC 22952–26001. (19th September 2018) - Weiss, S; Churilla, T; Chowdhury, I; Handorf, E; Collette, L; Collette, S; Alexander, B; Kocher, M; Soffietti, R; Claus, E
Abstract: Background: We sought to evaluate local control of brain metastases among patients treated with stereotactic radiosurgery (SRS) versus neurosurgical resection within EORTC 22952. Material and Methods: We performed a post-hoc analysis of EORTC 22952 and included patients treated per-protocol who had 1–2 brain metastases <4 cm. The primary endpoint was local recurrence (previously treated site) defined from time of randomization. We compared modality-specific local control by calculating cumulative incidence of local recurrence and competing risk regression to adjust for prognostic factors/competing mortality. Results: Of 268 patients analyzed, 57.5% underwent SRS and 42.5% underwent surgical resection. Median follow-up was 13.5months. Compared to SRS, patients undergoing surgery had larger tumors (median 20mm vs. 28mm, p<0.001), more single brain metastases (74% vs. 98%, p<0.001), and different locations (p<0.001). Overall, SRS was associated with improved local control (p=0.015) in unadjusted analyses, but absolute differences in local control decreased with time (p<0.001 (interaction)). Unadjusted cumulative incidence of local recurrence by modality (SRS vs. surgery, respectively) are listed: 3months (2.0% vs. 15.8%), 6months (9.8% vs. 29.1%), 9months (17.0% vs. 35.4%), 12months (22.9% vs. 37.2%), and 24months (28.5% vs. 40.2%). Local control was similar by modality in the WBRT group (p=0.398) while SRS exhibited improved local control than surgery in the non-WBRT group (p=0.012). In adjusted models, surgical patients had a much higher early (0-3months) risk of local recurrence compared to SRS patients HR[95%CI]=5.94[1.72–20.45], but their risk decreased with time: 3-6months=1.37[0.64–2.90], 6-9months=0.75[0.28–2.00]. At >= 9months, local control appeared superior for surgery: 0.36[0.14–0.93]. Increased risk of local recurrence was also associated with increasing tumor size (p=0.031) and absence of extracranial disease (p=0.044). Conclusion: In this exploratory analysis, SRS appeared associated with improved early local control of treated lesions compared to patients treated surgically, although the relative benefit decreased with time. Variation in baseline patient characteristics limit this analysis warranting further study.